Who speaks for Muslims? The role of the press in the creation and reporting of Muslim public opinion polls in the aftermath of London bombings in July 2005 - Sobolewska, M; Sundas, A (SAGE Publications, 2012)
Muslim public opinion polls are mostly taken at face value as the direct and unbiased voice of British Muslims, but as this article argues most of the public opinion polls are commissioned by the media and suffer from similar framing effects to those seen in the general media coverage of Muslims. At a time of national crisis, following the London terrorist attacks in 2005, it has become especially clear that the media have been following their pre-existing narrative on Muslims rather than responding to public interest. We analyse all public opinion polls conducted in the 18 months following the 7/7 attacks and all their broadsheet newspaper coverage to show that the media framing effects influence both the creation of Muslim opinion polls, and their reporting.